Application strategies by selective medium treated with entomopathogenic bacteria Serratia marcescens and Pseudomonas aeruginosa as potential biocontrol against Coptotermes curvignathus - Chin, Kit Ling; H'ng, Paik San; Lee, Chuan Li; Wong, Wan Zhen; Go, Wen Ze; Khoo, Pui San; Abdullah, Luqman Chuah; Ashaari, Zaidon (The Royal Society, 2021)
The success of microbial termiticides in controlling termites depends on the ability of microbes to grow in different media and the functionality of the microbes as a resistant barrier or toxic bait. This study was conducted to understand the mortality rate and behaviour changes of the subterranean termite Coptotermes curvignathus Holmgren introduced with different concentrations of Serratia marcescens strain LGMS 1 and Pseudomonas aeruginosa strain LGMS 3 using wood and soil as bacterial transfer medium. In general, higher concentration of bacteria in soil caused a reduction in tunnelling activity and wood consumption and an increase in mortality. However, application on wood revealed a different outcome. Wood treated with S. marcescens of 106 CFU ml-1 concentration proved to be more efficient as bait than higher concentration applications as it caused a high mortality rate while still highly palatable for termites. Wood or soil treated with S. marcescens concentration higher than 109 CFU ml-1 creates a high toxicity and repellent barrier for termites. Pseudomonas aeruginosa of 109 CFU ml-1 concentrations applied on wood served as a slow-acting toxic bait. However, the ability for S. marcescens and P. aeruginosa to survive on wood is low, which made the bait unable to retain a useful level of toxicity for a long period of time and frequent reapplication is needed.